Proceedings of the 11th ACM Multimedia Systems Conference 2020
DOI: 10.1145/3339825.3394934
|View full text |Cite
|
Sign up to set email alerts
|

A unified evaluation framework for head motion prediction methods in 360° videos

Abstract: The streaming transmissions of 360°videos is a major challenge for the development of Virtual Reality, and require a reliable head motion predictor to identify which region of the sphere to send in high quality and save data rate. Different head motion predictors have been proposed recently. Some of these works have similar evaluation metrics or even share the same dataset, however, none of them compare with each other. In this article we introduce an open software that enables to evaluate heterogeneous head m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As a result, the horizontal bias in VR only varied with mask types by its amplitude. We have shown that the head generally spans scenes with movements long in duration and amplitudes; consequently, future head movements during free-viewing can be predicted with a time-dependent model ( Nguyen et al., 2018 ; Rondón et al., 2020 ). Because in the displays’ frame of reference the eyes do not move significantly far from the centre ( Sitzmann et al., 2017 ), a big part of the peripheral content presented in the headset could be decreased in quality as a function of eccentricity, foveated rendering would allow compressing visual information further ( Weier et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the horizontal bias in VR only varied with mask types by its amplitude. We have shown that the head generally spans scenes with movements long in duration and amplitudes; consequently, future head movements during free-viewing can be predicted with a time-dependent model ( Nguyen et al., 2018 ; Rondón et al., 2020 ). Because in the displays’ frame of reference the eyes do not move significantly far from the centre ( Sitzmann et al., 2017 ), a big part of the peripheral content presented in the headset could be decreased in quality as a function of eccentricity, foveated rendering would allow compressing visual information further ( Weier et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The settings of the federated learning are as follows. In each round, all of K = 30 users update 2 According to the analysis in [2], [20], the traces of the first 20 users in the dataset have mistakes, thus we only use the traces of the other 30 users.…”
Section: Trace-driven Simulation Resultsmentioning
confidence: 99%
“…Spherical distance, known as orthodromic distance [2], [20], has been considered as the most appropriate metric to measure the viewpoint prediction error of FoV on the unit sphere [2]. As shown in Fig.…”
Section: E Prediction Error: Spherical Distancementioning
confidence: 99%
“…Thus, it is necessary to predict and cache the tile files that users may watch in advance, which requires the prediction of the users' head motion trajectory in the coming period. Related research [27] shows that various head motion prediction models have been proposed to predict short-term head trajectory changes with high accuracy in recent years. In the tile-based prediction model presented in the literature [5], prediction accuracy can reach 84.22% when the prediction period is set to 1s.…”
Section: Introductionmentioning
confidence: 99%